Customer Segmentation by Factors Influencing Brand Loyalty and Customer Involvement - Tereza Vebrová (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2016)
Brand loyalty and customer involvement are two important concepts that help explain and understand a significant part of consumer shopping behavior. The aim of the present work is to identify factors influencing brand loyalty and customer involvement. A further aim is to consider subsequent segmentation of customers with respect to different degrees of brand loyalty and customer involvement. The research was focused on the field of Czech telecommunication services – mobile operators. Primary data were acquired through the method of questionnaire survey. In total, the questionnaire was completed by 340 respondents, of which 319 respondents owned their mobile phones for private purposes only. For more accurate interpretation of the identified factors the Exploratory Factor Analysis method was used. Four factors of brand loyalty were extracted, which account for 75 % of the variability of the original parameters: (1) Cognitive affective loyalty, (2) Trustworthiness, (3) Attitudinal loyalty and (4) Commitment and three factors of customer involvement were found to account for 71 % variability of the original parameters: (1) Social involvement, (2) Centrality, (3) Importance. High loyalty customers mostly have only one SIM card and 73 % of them use a tariff. In a further group of highly involved customers own from 80 % only one SIM card. This study forms part of a research programme investigating the influence of customer involvement on brand loyalty.